Psychosocial and physical activity behaviour among adults with intellectual disabilities in Hong Kong. Issue 2 (2014) - ,
Abstract : Purpose – The purpose of this paper is to get information on the background, demographic data and the lifestyle of adults with intellectual disability in Hong Kong shelter workshop; to get information on physical activity behaviour and psychosocial behaviour of adults with intellectual disability in Hong Kong sheltered workshop; to assess the concurrent validity and reliability of the baseline interview questionnaire (BIQ‐C); and a trial run to test the feasibility on running a larger scale of study in future.Design/methodology/approach – Psychosocial behaviour was assessed by BIQ‐C (Heller et al., 2006) with sub‐scale self‐efficacy, outcome expectation, barrier to exercise; and physical activity assessment by pedometers. The participants completed the BIQ‐C with an interviewer on fifth day morning before started work. Both step counts were collected and activity data were recorded in a log book separately during working hours and non‐working hours on each four consecutive weekdays.Findings – The percentage of obesity was serious among adults with intellectual disability in HK, especially on women; and adults with intellectual disability had more walking step counts in non‐working time compared with that at working time, which was considered "low active" (5, 000‐7, 499 step per day) in physical activity level. Besides, both male and female participants had high outcome expectation, barrier to exercise and low self‐efficacy. Results showed that BIQ‐C was valid and reliable as an outcome measure to be used for intellectual disability.Research limitations/implications – The sample represented adults with mild to moderate intellectual disability which were based on a centre supervisor's confirmation, and then subjects were randomly selected to participate. The results were based on mild to moderate grade participants wearing pedometer for four consecutive days, for those who were unable to wear the pedometer by themselves were excluded from this study (severe intellectual disability). Moreover, the results only reflect the number of steps during weekdays, there was no data on weekends.Practical implications – Assessment tools are valid and reliable among adults with intellectual disability in Hong Kong. Study showed that running a larger scale of intervention is possible and feasible in sheltered workshop.Originality/value – There is relatively little information on the physical activity patterns and psychosocial behaviour of workers with intellectual disability in Hong Kong, intervention may help understanding and promote health in this population.